Examination of Tobacco-Related Messaging and Tobacco Use over Time among U.S. Military Young Adults. (2nd January 2023) - Pebley, Kinsey; Wang, Xin-Qun; Fahey, Margaret C.; Patten, Christi A.; Mallawaarachchi, Indika; Talcott, G. Wayne; Klesges, Robert C.; Little, Melissa A.
Abstract: Background: People from minoritized populations have historically been targeted by tobacco companies. Little is known about exposure to tobacco-related messages among military personnel from disadvantaged backgrounds. Objectives: The current study aimed to examine exposure to tobacco-related messaging across many nicotine products and through a variety of mediums (i.e., family, friends, advertisements, event promotions, social media) among diverse military populations and use one year later in a sample of young adults who recently enlisted in the U.S. Air Force. Methods: In this study, 8, 901 U.S. Air Force trainees reported on demographics, tobacco use, and exposure to positive tobacco messages from social sources (i.e., friends, family, social media) and environmental sources (i.e., advertisements and promotions). Tobacco use was reported one-year later. Results: Compared to others of the same reported racial/ethnic background, Latino/a/x (Relative Risk Ratio [RRR] = 1.354, 95% CI : [1.145, 1.563]) and multiracial (RRR = 1.594, 95% CI : [1.173, 2.016]) participants who were exposed to positive tobacco messages from social sources were significantly more likely to report tobacco product use at one-year follow-up than those who were not exposed to social messages. Exposure to positive tobacco messages from environmental sources were not significantly associated with tobacco use one year later. Conclusions: Social messages may play an important role in increasing risk of tobacco use among some minoritized populations. Cultural as well as systemic factors could be addressed in future tobacco prevention programs to decrease the potency of positive tobacco-related social messages among Latino/a/x and multiracial communities.